Advances in the Study of the Tick Cattle Microbiota and the Influence on Vectorial Capacity - Aguilar-Díaz, Hugo; Quiroz-Castañeda, Rosa Estela; Cobaxin-Cárdenas, Mayra; Salinas-Estrella, Elizabeth; Amaro-Estrada, Itzel (Frontiers in Veterinary Science, 2021)
The information from the tick cattle microbiota suggests that the microbial populations may modulate a successful infection process of the tick-borne pathogens. Therefore, there is a need to know the microbial population and their interactions. In this mini-review, we present several examples of how microbiota regulates the survival of pathogens inside the tick and contributes to fitness, adaptation, and tick immunity, among others. The communication between the tick microbiota and the host microbiota is vital to understanding the pathogen transmission process. As part of the tick microbiota, the pathogen interacts with different microbial populations, including the microorganisms of the host microbiota. These interactions comprise a micro-system that regulates the vectorial capacity involved in tick-borne diseases. The knowledge we have about the vectorial capacity contributes to a better understanding of tick-borne pathogens. Additionally, using approaches based on multi-omics strategies applied to studying the microbiota and its microbiome allows the development of strategies to control ticks. The results derived from those studies reveal the dynamics of the microbiota and potential targets for anti-tick vaccine development. In this context, the anti-microbiota vaccines have emerged as an alternative with a good prognosis. Some strategies developed to control other arthropods vectors, such as paratransgenesis, could control ticks and tick-borne diseases.